Wirkungsgeschichte and Visual Exegesis: The Contribution of Hans-Georg Gadamer - O'Kane, Martin 1952- (2010)
The article considers the visual dimensions associated with Wirkungsgeschichte. It accentuates the role of the artist as an active reader of the Bible and not merely as an illustrator of biblical scenes and highlights the approach of Hans-Georg Gadamer in appreciating the part played by the viewer, as well as the artist, in the visual hermeneutical process. The biblical story of the adoration of the Magi (Mt. 2.1-12), the first public and universal seeing of Christ and one of the most frequently depicted scenes in the entire history of biblical art, is used to illustrate Gadamer’s approach. The emphasis in the biblical narrative on the revealing of the Christ-child to the reader parallels a key concept in Gadamer’s hermeneutical aesthetics, namely Darstellung, a term that denotes how a painting facilitates its subject matter in coming forth, in becoming an existential event, an epiphany , in the life of the viewer.
Keywords: Epiphany; Darstellung; Visual Exegesis; Gadamer; Wirkungsgeschichte